Forgotten Elastic Band as an Unusual Cause of Limb Ulceration: Case Report and Review of the Literature - Keagan Werner-Gibbings; Liesl Ischia; Oleksandr Khoma; Robert Tang (Case Reports in Medicine)
We discuss a case of circumferential ulceration of the lower leg in a cognitively impaired elderly man with poor tissue integrity. Thorough clinical examination eventually determined the cause as being a circumferentially placed, forgotten elastic band causing ulceration via sustained tension around the limb. Circumferential application of an elastic band to an extremity is an exceedingly rare but serious cause of lower leg ulceration.